Flexural Toughness of Steel Fiber Reinforced High Performance Concrete Containing Nano-SiO2 and Fly Ash. (23rd April 2014) - Zhang, Peng; Zhao, Ya-Nan; Li, Qing-Fu; Wang, Peng; Zhang, Tian-Hang
Abstract : This paper aims to clarify the effect of steel fiber on the flexural toughness of the high performance concrete containing fly ash and nano-SiO2 . The flexural toughness was evaluated by two methods, which are based on ASTM C1018 and DBV-1998, respectively. By means of three-point bending method, the flexural toughness indices, variation coefficients of bearing capacity, deformation energy, and equivalent flexural strength of the specimen were measured, respectively, and the relational curves between the vertical load and the midspan deflection (P V - δ ) were obtained. The results indicate that steel fiber has great effect on the flexural toughness parameters and relational curves (P V - δ ) of the three-point bending beam specimen. When the content of steel fiber increases from 0.5% to 2%, the flexural toughness parameters increase gradually and the curves are becoming plumper and plumper with the increase of steel fiber content, respectively. However these flexural toughness parameters begin to decrease and the curves become thinner and thinner after the steel fiber content exceeds 2%. It seems that the contribution of steel fiber to the improvement of flexural toughness of the high performance concrete containing fly ash and nano-SiO2 is well performed only when the steel fiber content is less than 2%.